Synchrotron Investigation of Microporous Layer Thickness on Liquid Water Distribution in a PEM Fuel Cell. Issue 7 (1st April 2015) - Lee, J.; Yip, R.; Antonacci, P.; Ge, N.; Kotaka, T.; Tabuchi, Y.; Bazylak, A.
Abstract : Synchrotron X-ray radiography was utilized to visualize the liquid water distribution in a fuel cell with an active area of 0.48 cm 2 with an effective spatial resolution of 10 μm. Water content was measured in the gas diffusion layers (GDLs), where microporous layer (MPL) thicknesses ranged between 0 and 150 μm. The distribution of liquid water in a substrate-free polymer electrolyte membrane (PEM) fuel cell with a 50 μm-thick MPL was also determined. It was observed that the presence of an MPL significantly reduced the water content at the interfacial region between the catalyst layer and GDL, and increasing the thickness of the MPL led to a reduction of liquid water accumulation at the interface between the substrate and MPL.